Effect of folic acid supplementation on diminished ovarian reserve: study protocol of a single-centre, open-label, randomised, placebo-controlled clinical trial - Yan Wang; Ling Zheng; Kaijun Liao; Dongli Lu; Jiaxin Wu; Binjin Wu; Zhaochun Wu; Zhenghua Jiang (BMJ Open)
Introduction The prevalence of diminished ovarian reserve (DOR), a common gynaecological disorder, is approximately 10% across the world. Failure in early diagnosis and treatment may result in continuous decreases in ovarian function and the resultant loss in an opportunity of pregnancy, which greatly affects the happiness of the women’s family and women’s physical and mental health. Nevertheless, there has been no effective treatment for such a disorder until now. Folic acid, a member of the vitamin B family, is involved in one-carbon cycle and methylation regulation. It has been found that folic acid affects the whole period of pregnancy, and folic acid supplementation has shown effective to remarkably reduce the incidence of fetal neural tube defects and decrease plasma homocysteic acid levels, thereby resulting in a decline in the incidence of abortion. In addition, folic acid is reported to mediate ovarian functions. It is therefore hypothesised that folic acid may improve DOR.Methods and analysis A single-centre, open-label, randomised, placebo-controlled clinical trial is designed. We plan to recruit 140 women with DOR at ages of 30–35 years. All participants will be randomised into the folic acid group and placebo group, and each subject will be given a tablet with the same appearance daily for 6 months. The primary outcome is antral follicle count, and the secondary outcomes are ovarian reserve markers, ovarian low-dose stimulation responses and safety.Ethics and dissemination This study was approved by the Ethics Review Committee of Nanping First Hospital Affiliated to Fujian Medical University on 10 February 2021 (approval number: NPSY202002042). Written informed consent was obtained from all participants prior to randomisation, following a detailed description of the purpose of the study. The results of this clinical trial will be presented at scientific conferences and submitted to a peer-reviewed journal.Trial registration number Chinese Clinical Trial Registry, ChiCTR2100047410.